How are English lessons differentiated for linguistically gifted students by expert and novice English teachers? - Weckman, Laura (2017)
The purpose of this study is to describe the ways that expert and novice English teachers differentiate their teaching for linguistically gifted students, and to see whether these methods used differ based on teaching experience. I chose this topic because in my bachelor’s thesis I studied how expert teachers differentiate their teaching for the linguistically gifted students, and later on became interested whether the means used differed based on the amount teaching experience. The study was conducted using qualitative methods. Five female English teachers with approximately 10-30 years of teaching experience were interviewed to gather the data to represent expert English teachers. Novice teachers were a group of four female English teachers with less than three years of teaching experience. When asked to define differentiation all of the teachers talked about teaching so that everyone can learn. Most of the expert teachers put an emphasis on differentiation for weaker pupils where as novice teachers discussed differentiation from both perspectives. The study showed that expert and novice teachers used several different methods to differentiate learning for their students. Most of them were similar but differences were present in the amount of authentic material, technology and pupil involvement used.